2020
DOI: 10.1155/2020/8609213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Linking Oxidative Stress and Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is the most prevalent metabolic disorder characterized by chronic hyperglycemia and an inadequate response to circulatory insulin by peripheral tissues resulting in insulin resistance. Insulin resistance has a complex pathophysiology, and it is contributed to by multiple factors including oxidative stress. Oxidative stress refers to an imbalance between free radical production and the antioxidant system leading to a reduction of peripheral insulin sensitivity and contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
277
2
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 445 publications
(359 citation statements)
references
References 149 publications
2
277
2
22
Order By: Relevance
“…6 Then, the oxidative stress and other redox cascades initiated by interleukin (IL)-6, IL-8, and nuclear factor kappa-light-chain-enhancer of activated B cells take place, leading to progressive cell damage independent from the causative organisms. 6,25,26 Both Cu and Zn are considered as antioxidant micronutrients, which minimize the inflammatory conditions resulting from oxidative stress. Both elements also play significant roles in the immune system functions including the viability, differentiation, and function of the cells of innate and adaptive response and the production of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Then, the oxidative stress and other redox cascades initiated by interleukin (IL)-6, IL-8, and nuclear factor kappa-light-chain-enhancer of activated B cells take place, leading to progressive cell damage independent from the causative organisms. 6,25,26 Both Cu and Zn are considered as antioxidant micronutrients, which minimize the inflammatory conditions resulting from oxidative stress. Both elements also play significant roles in the immune system functions including the viability, differentiation, and function of the cells of innate and adaptive response and the production of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that diabetes can lead to DR by several mechanisms including the polyol pathway [5], non-enzymatic glycation [6], activation of protein kinase C [7], oxidative stress [8][9][10][11][12], and inflammation [13]. Oxidative stress is considered to be one of the crucial causative factors in the development of DR, in combination with other biochemical imbalances, leading to both structural and functional changes and also promoting an increased loss of capillary cells in the microvasculature of the retina [11,12]. In addition, a significant body of evidence supports the role of proinflammatory cytokines, chemokines, and other inflammatory mediators in the pathogenesis of DR, leading to chronic low-grade inflammation of the retina and eventually to neovascularization [14].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is involved in the pathogenesis of DN, which is the basis of EMT. MDA level reflects the ability of the body to resist oxidative stress, 37 and oxidative damage can be prevented by enhancing the activities of antioxidant enzymes, including CAT, GSH-Px, and SOD, which strengthen the response of the antioxidant defense system. 38 In this study, Formononetin significantly decreased the level of MDA, and increased SOD,GSH-Px, and CAT levels.…”
Section: Discussionmentioning
confidence: 99%